Factors associated with alcohol intake and alcohol abuse among women in Belo Horizonte, Minas Gerais State, Brazil - Ísis Eloah Machado; Francisco Carlos Félix Lana; Mariana Santos Felisbino-Mendes; Deborah Carvalho Malta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The main objective of this cross-sectional study was to analyze factors associated with alcohol consumption among adult women living in Belo Horizonte, Minas Gerais State, Brazil, in 2011. Data for Belo Horizonte were obtained from the VIGITEL system (Telephone-Based Surveillance of Risk and Protective Factors for Chronic Diseases). Alcohol use was defined as self-reported intake of at least one dose in the previous 30 days; alcohol abuse was defined as four or more doses on at least one occasion during the same period. Polytomous logistic regression was used to evaluate factors associated with alcohol use and abuse. Alcohol use was more prevalent among women 25 to 34 years of age. Alcohol abuse was associated with age, schooling, health status, and smoking. The results suggest the need for policies to prevent alcohol abuse among women, especially targeting those who are younger, single, smokers, and with more education.